PENGARUH DOSIS MULSA JERAMI PADI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI (Brassica juncea L.) - Oematan, Shirly S.; Ndiwa, Antonius S. S.; Taga, Kornelis Djo (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2022)
This research was conducted in Oematnunu Village, West Kupang District, Kupang Regency. The aim of this research was to determine the effect of rice straw mulch dose on the growth and yield of mustard (Brassica juncea L. ) and to get the right dose of rice straw mulch that can provide the best growth and yield of mustard plants. This study is a single factor experiment designed in a completely randomized design (CRD) with 5 treatments in the form of doses of rice straw mulch. Each treatment combination was repeated 6 (six) times so that a total of 30 experimental units were obtained.The results showed that 1). The dose of rice straw mulch treatment had a very significant effect on the height of the mustard plant, the increase in the number of leaves, the fresh gross weight of the mustard plant and the net weight of the mustard plant. Single factor treatment separately for each single factor treatment level of rice straw mulch dosage had a significant and very significant effect on most of the observation variables, in the form of increase in plant height, increase in number of leaves, fresh gross weight of mustard plants and net weight of mustard plants. 2). The interaction treatment level of dose of rice straw mulch of 20 tons/ha or equivalent to 200 grams/polybag is the best interaction treatment on plant height, number of leaves, total fresh gross weight of mustard plant and total net weight of mustard plant, each of which is plant height. 40.62 cm, the number of leaves 8.67 strands, the total plant fresh weight was 474.78 grams and the total plant net weight was 422.45 grams.